Preliminary study on the self-assembly of a pair of azobenzene liquid crystals derived from alanine. Issue 1 (13th August 2022) - Wu, Limin; Chu, Jinming; Wang, Fei; Liu, Wei; Guo, Yongmin; Li, Yi; Li, Baozong; Yang, Yonggang
Abstract: A series of azobenzene liquid crystals containing one amino acid residue were synthesized. They exhibit smectic mesophases. The compounds derived from alanine can self-assemble into twisted nanoribbons. The molecules organized in a monolayer structure within the nanoribbon. Circular dichroism characterization indicated that the neighboring liquid crystal cores packed in a chiral structure. FT-IR spectra indicated that the nanoribbons were caused by H-bonding and association of hydrocarbon chains.